PROSEDUR KONFIRMASI PIUTANG USAHA PT ABC OLEH KAP TST - Elovani, Yunike Christie; Sunani, Avi (Universitas Muhammadiyah Metro, 2025)
Accounts receivable confirmation procedures are steps taken by the company to ensure that the amount of receivables presented in the company's books matches the amount recognized by the debtor. This study aims to analyze the accounts receivable confirmation procedure applied by PT ABC by referring to the Public Accountant Professional Standards (SPAP) and the theory of accounts receivable confirmation procedures. This research is useful for anticipating and understanding the risks and validity of accounts receivable balances. The research method applied is a qualitative method using library research techniques, field research, and interviews. The results of this study indicate that PT ABC uses a systematic sample selection technique for confirmation of accounts receivable, and the form of confirmation used is positive confirmation. The auditor will apply an alternative procedure, namely the open invoice procedure when the debtor does not answer the confirmation letter sent by the auditor. The implication of this research is to assist PT ABC in identifying potential payment problems and improving the reliability of its financial data. Based on the results of the analysis carried out, it can be concluded that the theory of accounts receivable confirmation procedures and Public Accountant Professional Standards (SPAP) support the accounts receivable confirmation procedures applied by KAP TST & Rekan.